Pengaruh Pengetahuan Keuangan dan Sikap Keuangan terhadap Keputusan Berinvestasi Masyarakat di Kota Banda Aceh - Milzam Wafa Staqif; Zuraidah Zuraidah; Syahrul Maulidi (Politeknik Kampar, 2026)
This study aims to analyze the effect of Financial Knowledge and Financial Attitude on Investment Decisions among the community in Banda Aceh City. Investment activities have become increasingly important as individuals seek ways to manage their finances and improve their long-term financial well-being. Therefore, understanding the factors that influence investment decisions is essential. This research employed a quantitative approach using a survey method with 100 respondents selected through purposive sampling. The data collected from the respondents were then analyzed using multiple linear regression to determine the influence of each variable. The results indicate that Financial Knowledge and Financial Attitude partially and simultaneously have a positive and significant effect on Investment Decisions. Among these variables, Financial Attitude shows a more dominant influence in shaping individuals’ investment behavior, although the overall contribution of both variables remains relatively low. These findings suggest that individuals with better financial understanding and more positive Financial Attitudes tend to make more rational investment choices.